Environmental innovation activities and patenting: Germany reconsidered. Issue 7 (3rd July 2017) - Rave, Tilmann; Goetzke, Frank
Abstract : This paper provides new econometric evidence on the determinants of eco-innovations by using multiple innovation indicators and by combining survey-based information and patent records at the firm level from two different time periods. We hypothesize that firms with a propensity to patent focus on future technological and market opportunities and do not directly or immediately react to incentives created by environmental policies. Based on negative binomial models, we confirm that eco-patents are stimulated by the expectation of creating technological advancement and new market opportunities. By contrast, energy cost savings can better or more easily be achieved when firms refrain from patenting and concentrate on non-patented innovations or adoption. Favorable framework conditions created by environmental policies and patent protection are also important for eco-patenting, but more in the longer term. Testing the validity of using self-reported eco-innovations, instead of patents, as the dependent variable in simple binomial probit models reveals that product eco-innovations as reported in the surveys are a relatively good proxy for eco-patents. Yet, for product eco-innovations, serving and enlarging current markets is another important reason to innovate.